Application of Double Deposition and Stripping Steps System for Minimization of Interferences of Peaks' Overlapping in Anodic Stripping Voltammetry. Issue 3 (10th August 2022) - Gęca, Iwona
Abstract: An anodic stripping voltammetric procedure for the determination of bismuth in the presence of excess of Cu 2+ ions at two ex situ plated gold film electrodes was described. The procedure is based on utilization of two deposition and two stripping steps system. The presented procedure ensures increasing the sensitivity of Bi 3+ determination and minimization of interferences related to peaks' overlapping. The calibration graph for bismuth determination was linear from 2.5×10 −9 to 2×10 −8  mol L −1 for deposition time of 300 s at both working electrodes while detection limit was 7.7×10 −10  mol L −1 . Abstract :